A STABILITY INDICATING ION-PAIR LC METHOD FOR THE DETERMINATION OF ASENAPINE IN PHARMACEUTICALS - Sakine Atila Karaca; Duygu Yeniceli Uğur (Journal of the Chilean Chemical Society, 2017)
In this study, a new, simple and specific stability indicating ion-pair LC method was developed and fully validated for the determination of asenapine in tablets. The analysis was performed on an Agilent Eclipse XDB-C8 column (4.6 x 150 mm, 3.5 μm particles) at 30˚C. A mixture of phosphate buffer (pH 3, 20 mM) containing 10 mM 1-heptane sulfonic acid and acetonitrile, (60:40, v/v) at a flow rate of 1 mL min-1 was used as mobile phase. Detection was performed by a diode array detector at 220 nm. The developed method was validated according to related ICH guideline and US Pharmacopeia and it was suitable in terms of accuracy, precision, specificity, robustness and stability. The method was linear in the concentration range of 0.5-100 μg mL-1. Limit of detection and limit of quantification values were calculated as 0.0836 μg mL-1 and 0.2788 μg mL-1, respectively. This ion-pair LC method was applied successfully for the determination of asenapine in its sublingual tablets.